2001
DOI: 10.1177/135245850100700608
|View full text |Cite
|
Sign up to set email alerts
|

Visuoperceptual impairment in MS patients: nature and possible neural origins

Abstract: Failures on visuoperceptual neuropsychological tasks (on neuropsychological tests of visuo-spatial perception or on tests concerning semantic properties of visual objects), may indicate focal deficits of visuoperceptual function, or could be the result of (an)other (peripheral) visual deficit(s), or be the effect of a more general cognitive decline. In multiple sclerosis (MS) patients exhibiting sufficient visual acuity and not showing severe cognitive deterioration, impairment on a comprehensive set of 31 vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Previous studies on cognitive impairment in MS patients have not classified cognitively intact persons with poor visuospatial functions as a separate group; however, they also found a relationship between visuospatial functions and global cognitive functioning in MS patients [23]. When this profile was analyzed by comparing scores on other cognitive functions, these subjects were found to have better cognitive functioning in the domains of recall (immediate and delayed), attention, and verbal fluency compared to subjects classified as CD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on cognitive impairment in MS patients have not classified cognitively intact persons with poor visuospatial functions as a separate group; however, they also found a relationship between visuospatial functions and global cognitive functioning in MS patients [23]. When this profile was analyzed by comparing scores on other cognitive functions, these subjects were found to have better cognitive functioning in the domains of recall (immediate and delayed), attention, and verbal fluency compared to subjects classified as CD.…”
Section: Discussionmentioning
confidence: 99%
“…Within the MS group, 35.2% of all subjects were classified as CIVSI profile. Although visuospatial functions have received less consideration in the literature [3], around 25% of MS patients have been reported to have a deficit in visual perceptional functions [23]. Another important aspect of this latent profile is visuomotor integration and planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnocellular deficits have been proposed to represent a behavioural correlate of demyelination in ON patients [31,32]. However, it is interesting to note that in ON patients, the deficit in processing LSF only occurs in terms of error rate and not in terms of reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that impairment in these domains occurs with considerable frequency in MS [33][34][35][36], although less commonly than in the domains of processing speed and memory. For example, in an extensive battery of visuospatial tests, Vleugels and colleagues reported visuoperceptual deficits in MS patients that were relatively independent of other cognitive or visual problems [37]. The authors suggested that this pattern of visuoperceptual impairment may represent a focal deficit.…”
mentioning
confidence: 97%